Revitalisasi Desa Dalam Konstelasi Desentralisasi Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Timotius, Richard (UI Scholars Hub, 2018)
In the New Order period, the village was arranged separately in Law No. 5 of 1979, which adopted the uniformity of such a village in Java, precisely causing the existence of customary law community outside Java experienced a tremendous reduction. Law No. 6 of 2014 finally accommodate the existence of indigenous villages and villages. This paper used normative juridical research method which result that the existence of Law Number 6 Year 2014 regarding Village is a form of revitalization of previous regulation. The revitalization covers the arrangement of village authority, village finance arrangement, village government management and rural development and community participation